Native Aquatic and Wetland Plants: Duck Potato, Sagittaria lancifolia - Kimberly A. Moore; Luci E. Fisher; Carl J. Della Torre; Lyn A. Gettys (EDIS)
This 3-page fact sheet discusses the classification, description, habitat, propagation, and uses of duck potato, an aquatic perennial that typically grows in swampy ground or standing water in ponds, lakes, streams, and ditches and usually blooms in the spring. Written by Kimberly A. Moore, Luci E. Fisher, Carl J. Della Torre III, and Lyn A. Gettys, and published by the UF Department of Agronomy, December 2015.